(untitled) (Theatrum historiae, 2019)
Research into the issue of patronage in the Polish-Lithuanian Commonwealth, undertaken once by Antoni Mączak, is continuing to this day. However, researchers are focusing their attention primarily on the functioning of informal interrelations in the magnate and nobility environment of the seventeenth century. Although detailed studies have provided us with numerous findings, this remains a wide, extremely complex and rich subject, and researchers constantly stipulate the need for further studies. The vast majority of scholars focus mainly on male patron-client relations. They seek these ties in a court, military and dietine (sejmiki) environment. The subject of the male magnate court and its impact on society seems to be very significant to many historians. Interestingly, the male magnate court was also the place of patrons’ private political actions. A substantial issue of cliental ties involved in the magnates’ economy (latifundia) remains the focus of interest of researchers to this day. Some of them perceive clientelism as a religiously conditioned phenomenon (for example, ecclesiastical foundations), at the same time highlighted by cultural patronage and attempts to build the power of families based on a prestige policy. Research on clientelism in relation to the eighteenth century is not sufficient. The existing research does not cover these complex issues, particularly in relation to the Saxon period. Moreover, these works date back to the previous century and do not take into account any new findings. The Saxon era, when cliental ties became particularly important due to the dysfunctions of the most important state institutions, represents a rich source of research material. Unfortunately, studies on this period are too scarce and discouraging, and only a small group of researchers are currently examining the issue of clientelism in the Saxon era. Speaking of clientelism in the Commonwealth in general terms, one very important issue requires closer examination. This is the fact that while this problem is well recognized and defined in European historical science, in current Polish research there are almost no works which deal with the issue of female patronage and women’s role in forming a cliental background. The few studies devoted to the issue of women’s presence in the development of cliental ties in the Saxon era only indicate the need for further research on the phenomenon of female patronage. However, they do not present a thorough and multifaceted investigation. This is the very reason for our interest in female patronage and willingness to undertake in-depth research on this issue.